1993
DOI: 10.1128/aac.37.2.349
|View full text |Cite|
|
Sign up to set email alerts
|

In vitro antimicrobial activity of CP-99,219, a novel azabicyclo-naphthyridone

Abstract: CP-99,219 is a trifluoronaphthyridone with significant antibacterial activity that includes the family Enterobacteraceae (MICs for 90% of the strains tested [MIC90s], <0.015 to 0.5 ,ug/ml), MoraxeUla catarrhalis, Haemophilus influenzae, and gonococci (MICs, <0.015 p.g/ml). LegioneUla spp. were also CP-99,219 susceptible, with MICs of 0.008 to 0.12 ,ug/ml. 219 demonstrated activity greater than that of ciprofloxacin, ofloxacin, or enoxacin against Pseudomonas aeruginosa (MICg., 1 p,g/ml), Xanthomonas maltophil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
21
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(25 citation statements)
references
References 7 publications
4
21
0
Order By: Relevance
“…The activity of CP 99,219 against B. fragilis in a previous preliminary report parallels the findings in the current study (14). The MIC90 of >8.0 jig/ml for CP 99,219 against B. fragilis reported in the paper by Gooding and Jones (13) represents an error; the MIC90 was, in actuality, 0.5 jig/ml (16), which is similar to values reported in this study.…”
supporting
confidence: 79%
See 1 more Smart Citation
“…The activity of CP 99,219 against B. fragilis in a previous preliminary report parallels the findings in the current study (14). The MIC90 of >8.0 jig/ml for CP 99,219 against B. fragilis reported in the paper by Gooding and Jones (13) represents an error; the MIC90 was, in actuality, 0.5 jig/ml (16), which is similar to values reported in this study.…”
supporting
confidence: 79%
“…The 1-N substitution of CP 99,219 is a difluorinated structure identical to that of tosufloxacin that produces enhanced activity against some ciprofloxacinresistant strains. CP 99,219 possesses a broad spectrum of activity against gram-positive and -negative organisms, including those resistant to ciprofloxacin (9,10,13,14,18,21 …”
mentioning
confidence: 99%
“…Many investigators (8,13,14,23) have reported that trovafloxacin (CP-99,219) has potent in vitro activity against grampositive bacteria, including streptococci, such as S. pneumoniae and Streptococcus pyogenes, and enterococci (i.e., Enterococcus faecalis). This enhanced in vitro activity against gram-positive pathogens has not diminished the compound's gram-negative antimicrobial spectrum.…”
mentioning
confidence: 99%
“…As trovafloxacin demonstrates a broad spectrum of activity against gram-positive and gram-negative aerobes and anaerobes (2,7,10,12,19), treatment of a wide range of serious pediatric infections is possible. In particular, the in vitro activity of trovafloxacin against S. pneumoniae is excellent, with the drug having similar activity against both penicillin-susceptible and nonsusceptible strains (11,17,19).…”
Section: Discussionmentioning
confidence: 99%